A research and development effort in developing the optimal formulations for new tablet drugs using design of experiments: part 2 (bioequivalence studies). (1st January 2012) - Li, Zhe; Cho, Byung Rae; Melloy, Brian J.
As an extension to the dissolution comparison studies in Part 1, this paper further examines the optimal levels of inactive ingredients of a formulation, when excipient changes occur which require crossover designs be performed to demonstrate bioequivalence between the pre-change and post-change formulations. In this paper, a standard 2 × 2 crossover study, as a special type of experimental design, is integrated into the ordinary framework. In addition to the discrete computational method for assessing bioequivalence that is suggested by the FDA, we further develop a continuous method to calculate critical quality characteristics. Incorporating the Taguchi quality loss concept and regulatory requirements, we propose an enhanced formulation optimisation model by simultaneously considering both the mean and variance of related characteristics. A numerical example is given to verify the effectiveness of our proposed approach. Additionally, the simulated results show that the continuous assessment method produces more desirable optimal formulations than the discrete one.